2000
DOI: 10.1021/bp990143t
|View full text |Cite
|
Sign up to set email alerts
|

Production of Functional Hepatocyte Growth Factor (HGF) in Insect Cells Infected with an HGF-Recombinant Baculovirus in a Serum-Free Medium

Abstract: Three insect cell lines, SL-7B cells derived from Spodoptera litura, Sf9, and High Five (Hi-5) cells, were used for the production of pro-hepatocyte growth factor (pro-HGF). Cells were cultured and then infected with a recombinant HGF-containing baculovirus in a serum-free medium. In SL-7B cells, pro-HGF is synthesized and excreted from the cells and late in infection is converted to a heterodimeric form of HGF even when the cells are grown in serum free medium. Conversion of a single-chain form of HGF (pro-HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, the rcHGF product obtained should be further purified before the studies start. The generation of rcHGF was higher than the previously reported production of rhHGF using insect (Wang et al, 2000;Yee et al, 1993) or mammalian cells (Nakamura et al, 1989). The use of other production systems, for instance the yeast Pichia pastoris (Liu et al, 2005) may yield even higher quantities of >500 mg/L recombinant HGF.…”
Section: Discussionmentioning
confidence: 71%
“…However, the rcHGF product obtained should be further purified before the studies start. The generation of rcHGF was higher than the previously reported production of rhHGF using insect (Wang et al, 2000;Yee et al, 1993) or mammalian cells (Nakamura et al, 1989). The use of other production systems, for instance the yeast Pichia pastoris (Liu et al, 2005) may yield even higher quantities of >500 mg/L recombinant HGF.…”
Section: Discussionmentioning
confidence: 71%
“…Since the concentration of native HGF in plasma is very low, purification of HGF from plasma is very difficult. It was reported that HGF is expressed in foreign gene expression systems such as mammalian cells, CHO cells [22,23] , insect cells [24] , and gene therapy [25] . Dang et al [26] and Li et al [27] .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several earlier attempts to express biologically active recombinant human HGF (rh-HGF) in both Escherichia coli and insect cells (13, 14). Although biological activity of rh-HGF produced from E.coli has been reported to be equivalent to its native form (15), the absence of the disulfide bond formation and lack of molecular glycosylation can potentially compromise its applicability in vivo.…”
Section: Introductionmentioning
confidence: 99%